The Edinburgh companion to Virginia Woolf and contemporary global literature - Dubino, Jeanne, 1959-; Pajak, Paulina; Hollis, Catherine; Lypka, Celise; Neverow, Vara (Edinburgh companions to literature and the humanities., 2021)
"To capture the many Woolfian currents circulating around the world, the twenty-three chapters in this companion examine the global responses Woolf’s work has inspired and explore her worldwide influence. Authors address ways Woolf is received by writers, publishers, reading audiences and academics in countries around the world; how she is translated into multiple languages; and the transformation of her life into global contemporary biofiction. This collection is dialogic and comparative, incorporating both transnational and local tendencies insofar as they epitomize Woolf’s global reception and legacy. It contests the ‘centre’ and ‘periphery’ binary, offering new models for Woolf global studies and promoting cross-cultural understandings" --